The Influence of Firm Size, Leverage, and Profitability on The Timeliness of Financial Reporting in Manufacturing Industry Companies - Sherlyta Dwie Suwarno Putrri; Ahmad Fahrudin Alamsyah (Akuntansi: Jurnal Akuntansi Integratif, 2025)
The timeliness of financial reporting is an important element in the context of corporatetransparency and accountability, especially for entities engaged in the manufacturing industrysector on the IDX. This study aims to empirically investigate the effect of independentvariables, namely company size, leverage, and profitability, on the timeliness of financialreporting during the 2021-2023 period. Adapting a quantitative methodology approach, thisstudy relies on regression models used to analyze secondary data from the annual reports of37 companies selected using purposive sampling techniques based on a set of inclusioncriteria. The results show that firm size has a significant positive effect on the timeliness offinancial reporting, while leverage and profitability have a negative effect. Simultaneously,firm size, leverage, and profitability are shown to have a significant effect on the timeliness offinancial reporting, which indicates a complex interaction between these factors in the timelypresentation of financial statements